Human behavior and the social environment, micro level : individuals and families - Van Wormer, Katherine S. (Oxford University Press, 2017)
Unique to Human Behavior and the Social Environment, Micro Level is the focus on trauma and resilience in its exploration of human behavior across the life span. Illustrations are drawn from the arts as well as recent brain research from recent biological research.